1993
DOI: 10.1007/bf00871733
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic fungi and their cellulolytic and xylanolytic enzymes

Abstract: Anaerobic fungi are the inhabitants of the digestive tract of herbivorous mammals, ruminants as well as non-ruminants. One of the major characteristics of all anaerobic fungi examined thus far, is their production and secretion of a range of polysaccharide-degrading enzymes, including cellulases, xylanases and glucoside-hydrolases. The cellulolytic enzymes of the anaerobic fungus Neocallimastix frontalis have been shown to possess a high activity. Therefore anaerobic fungi and/or their enzymes could be interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…AF are now classified in a single order (Neocallimastigales) within the recently erected phylum Neocallimastigomycota (Hibbett et al, 2007). Originally described in sheep, members of the AF have since been shown to exist in the rumen, hindgut, and feces of ruminant and non-ruminant herbivorous mammals, as well as reptilian herbivores (Bauchop, 1979;Teunissen and Op den Camp, 1994;Mackie et al, 2004). Currently, only 6 genera and 20 species have been described (Griffith et al, 2009), although multiple uncharacterized isolates have also been reported (Philips and Gordon, 1989;Ho and Barr, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…AF are now classified in a single order (Neocallimastigales) within the recently erected phylum Neocallimastigomycota (Hibbett et al, 2007). Originally described in sheep, members of the AF have since been shown to exist in the rumen, hindgut, and feces of ruminant and non-ruminant herbivorous mammals, as well as reptilian herbivores (Bauchop, 1979;Teunissen and Op den Camp, 1994;Mackie et al, 2004). Currently, only 6 genera and 20 species have been described (Griffith et al, 2009), although multiple uncharacterized isolates have also been reported (Philips and Gordon, 1989;Ho and Barr, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most complex natural cellulose-digesting ecosystems exists in the rumen fluid of cows [30]. Although rumen microorganisms are capable of digesting cellulose, exogenous cellulase added to animal feed can increase the utilization of cellulosic feedstocks even in ruminant animals [31].…”
Section: Resultsmentioning
confidence: 99%
“…The cellulolytic enzymes produced by the fungi such as Neocallismastix sp. and Piromyces sp., also include both multicomponent complexes and free enzymes which are highly active and are able to degrade wider range of substrates than the bacteria [20,21]. The cellulases and xylanases produced by the protozoans lack the multimodular organization displayed by the bacterial and fungal enzymes, and are secreted into food vacuoles [18].…”
Section: Enzymes For Biomass Hydrolysismentioning
confidence: 99%